Genetic diversity and population structure of core watermelon (Citrullus lanatus) genotypes using DArTseq-based SNPs - Yang, Xingping; Ren, Runsheng; Ray, Rumiana; Xu, Jinhua; Li, Pingfang; Zhang, Man; Liu, Guang; Yao, Xiefeng; Kilian, Andrzej (Cambridge University Press, 2016)
Watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai var. lanatus] is an economically important vegetable belonging to the Cucurbitaceae family. Genotypes that exhibit agronomically important traits are selected for the development of elite cultivars. Understanding the genetic diversity and the genotype population structure based on molecular markers at the genome level can speed up the utilization of diverse genetic resources for varietal improvement. In the present study, we carried out an analysis of genetic diversity based on 3882 SNP markers across 37 core watermelon genotypes, including the most widely used watermelon varieties and wild watermelon. Based on the SNP genotyping data of the 37 watermelon genotypes screened, gene diversity and polymorphism information content values across chromosomes varied between 0.03–0.5 and 0.02–0.38, with averages of 0.14 and 0.13, respectively. The two wild watermelon genotypes were distinct from cultivated varieties and the remaining 35 cultivated genotypes were differentiated into three major clusters: 20 genotypes were grouped in cluster I; 11 genotypes were grouped in cluster II; three advanced breeding lines of yellow fruit flesh and genotype SW043 were grouped in cluster III. The results from neighbour-joining dendrogram, principal coordinate analysis and STRUCTURE analysis approaches were consistent, and the grouping of genotypes was generally in agreement with their origins. Here we reveal the genetic relationships among the core watermelon genotypes maintained at the Jiangsu Academy of Agricultural Sciences, China. The molecular and phenotypic characterization of the existing core watermelon genotypes, together with specific agronomic characteristics, can be utilized by researchers and breeders for future watermelon improvement.